PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PEMILIK IPHONE(Studi Pada Mahasiswa S1 Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro - Muhammad Fadhli Dzil Akbar; Nawazirul Lubis; Sari Listyorini (Universitas Diponegoro, 2016)
This research is motivated by the phenomenon of the development of smartphones, where competition between companies is getting tougher smartphone. Apple is a company engaged in the field of hardware and software, including hardware made by Apple is the Iphone. Apple is proving to be one of the big companies, it is derived from Apple's global sales reached 150 million units, but in Indonesia according to TBI in 2011 through 2013 the percentage is only able to control less than 5%, as well as on sales in Semarang according Sinarmas Mobile for 4 months experienced a low point only the highest selling 12 units and 18 units. The purpose of this study was to determine the effect of brand image and product quality to eputusan purchase iPhone. This type of research is explanatory research, with data collection through a questionnaire, literature study and interviews. The sampling technique using census techniques using research instrument questionnaire. The sample in this study amounted to 58 respondents who are iPhone users on S1 students FISIP Diponegoro University. This study uses linear regression analysis techniques and the significance test is used to prove the hypothesis using SPSS for windows version 20.0. The results showed that the brand image (X1), and product quality (X2), both jointly and individually a positive influence on purchase decisions dependent variable (Y). Simultaneously the brand image, product quality, has an influence on purchasing decisions by 40.7% according to multiple regression. Suggestions from this study is that Apple needs to improve the quality of products on the batteries to meet the needs of consumers and strengthen the brand image on promotional products.